Zambia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper analyzes sources of growth in Zambia. It assesses domestic debt dynamics and expenditure composition under two scenarios: first, the execution of the fiscal adjustment envisaged in the 2004 budget and in the medium-term framework; and second, the continuation of recent trends. The paper assesses movements in the external value of the kwacha using a number of different approaches. It also looks at developments in the real exchange rate and in differentials in rates of return on financial assets in Zambia and key financial centers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet